Photocatalytic degradation of methyl orange by CeO2 and Fe-doped CeO2 films under visible light irradiation - Channei,D. (Nature Publishing Group, 2015)
Undoped CeO2 and 0.50-5.00 mol% Fe-doped CeO2 nanoparticles were prepared by a homogeneous precipitation combined with homogeneous/impreganation method, and applied as photocatalyst films prepared by a doctor blade technique. The superior photocatalytic performances of the Fe-doped CeO2 films, compared with undoped CeO2 films, was ascribed mainly to a decrease in band gap energy and an increase in specific surface area of the material. The presence of Fe31 as found from XPS analysis, may act as electron acceptor and/or hole donor, facilitating longer lived charge carrier separation in Fe-doped CeO2 films as confirmed by photoluminescence spectroscopy. The 1.50 mol% Fe-doped CeO2 film was found to be the optimal iron doping concentration for MO degradation in this study.